The role of Porphyromonas gingivalis in atherosclerosis - Szulc, Małgorzata; Radwan-Oczko, Małgorzata (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
In recent years there have been a lot of studies on the link between periodontitis and atherosclerosis, which is a risk factor for many diseases. Periodontitis is connected with bacteria existence and as such can magnify the scale of general inflammation. It can either cause endothelium dysfunction leading to early stages of arteriosclerosis or accelerate the creation of atheromatous plaque and its destabilization. The direct evidence for the above-mentioned relation is the existence of classic periopathogens in the atheromatous plaque. They get to the circulation system from the periodontal pocket through its epithelium which is damaged with inflammation. The most commonly isolated bacteria is the Gram-negative anaerobe Porphyromonas gingivalis . The aim of this study was to present the mechanisms how Porphyromonas gingivalis causes the damage of endothelium and initiates atheromatous plaque formation as well as sustains chronic inflammation of the organism.